2014
DOI: 10.17221/7620-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Selected serum biochemical parameters and acute phase protein levels in a herd of Saanen goats showing signs of pregnancy toxaemia

Abstract: ABSTRACT:The purpose of this study was to examine selected serum biochemical parameters and acute phase protein levels in a herd of Saanen goats showing signs of pregnancy toxaemia. Seventy five female goats were used and divided into three groups. Group 1 (n = 57) (blood serum glucose levels were within the physiological range), Group 2 (n = 11) (serum glucose values were low) and Group 3 (n = 7) (serum glucose values were high). Goats in Groups 2 and 3 were diagnosed with pregnancy toxaemia. Apart from serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 21 publications
5
25
2
4
Order By: Relevance
“…Pregnancy toxemic goats in the present study showed a significant increase in the serum GGT, which was attributed to damage in liver parenchyma. Our results are confirmed by ultrasonographic examination of the liver in goats with PT which showed an increase in the echogenicity mainly "fatty liver" (Tontis and Zwahlen, 1987) which confirmed by postmortem findings in dead cases,the liver was pale yellow, slightly swollen and friable, similar results recorded by (Albay et al, 2014;Abba et al, 2015). Histopathologically, the liver showed fat globules distending the hepatocyte nuclei to the periphery with moderate lipidosis.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 86%
“…Pregnancy toxemic goats in the present study showed a significant increase in the serum GGT, which was attributed to damage in liver parenchyma. Our results are confirmed by ultrasonographic examination of the liver in goats with PT which showed an increase in the echogenicity mainly "fatty liver" (Tontis and Zwahlen, 1987) which confirmed by postmortem findings in dead cases,the liver was pale yellow, slightly swollen and friable, similar results recorded by (Albay et al, 2014;Abba et al, 2015). Histopathologically, the liver showed fat globules distending the hepatocyte nuclei to the periphery with moderate lipidosis.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 86%
“…Urine analysis showed aciduria and ketonuria in the present study might be due to increase the glucose demand than the dietary supply in pregnancy leading to increase the mobilization of long chain fatty acids from adipose tissues a marked rise in circulating non esterified fatty acid and ketone bodies, which in return, descend in urine (Gonzalez et al, 2011;Albay et al, 2014).…”
Section: Resultsmentioning
confidence: 48%
“…Under conditions of insufficient energy supply, alimentary ketogenesis decreases and the rate of hepatic ketogenesis from NEFA increases disproportionately (Albay et al, 2014). The liver now becomes the main and eventually almost the sole ketogenic organ.…”
Section: Discussionmentioning
confidence: 99%
“…Such metabolic changes are associated with marked increases in the mobilization rate of the long-chain fatty acids of adipose tissues and a marked rise in circulating concentrations of NEFA and ketones. During hyperketonaemia, ketone bodies are readily oxidised, serving as fuel for energy production (Albay et al, 2014;Cal-Pereyra et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation